Influência de Lactobacillus rhamnosus na patogenicidade e na expressão de genes de virulência de Candida albicans: estudo in vitro e in vivo - Ribeiro, Felipe de Camargo [UNESP] (2015)
The high incidence of candidiasis caused by Candida albicans and the adaptability of this species, as well as resistance to antifungal drive the development of research on alternative therapies to control this infection. The aim of this study was to evaluate the influence of Lactobacillus rhamnosus and products of their metabolism against C. albicans, evaluating the pathogenicity and the expression of genes that regulate the formation of C. albicans biofilms in vitro and in vivo in invertebrate model Galleria mellonella. Strains of C. albicans ATCC 18804 and L. rhamnosus ATCC 9595 were used (from the Microbiology Laboratory of the Institute of Science and Technology of São José dos Campos / UNESP). For the study were prepared from L. rhamnosus two suspensions, one containing the serving cell and the other with the culture supernatant free cells. The study of in vitro pathogenicity of C. albicans was assessed by biofilm formation testing and quantitation of CFU / ml of C. albicans, analysis of metabolic activity by XTT method and C. albicans filamentation. The analysis of the Galleria mellonella survival curve was used to evaluate in vivo the influence of L. rhamnosus in infection caused by C. albicans. Genes, BCR1, EFG1, CPH1, HWP1, ALS1 and ALS3 of C. albicans were quantified by RT-PCR after interacting in biofilm model. In vitro evaluation L. rhamnosus was able to inhibit biofilm formation, filamentation and reduce the metabolic activity of C. albicans. These effects were also observed when using the suspension culture supernatant of L. rhamnosus, indicating the possible of production substances with inhibiting effect. The results obtained in vivo indicate that L. rhamnosus and its supernatant protected G. mellonella of C. albicans infection, but the suspension of the supernatant showed better results, as it increased the survival caterpillar G. mellonella. The results of gene expression have shown that ....